2016
DOI: 10.1261/rna.055756.115
|View full text |Cite
|
Sign up to set email alerts
|

Data-directed RNA secondary structure prediction using probabilistic modeling

Abstract: Structure dictates the function of many RNAs, but secondary RNA structure analysis is either labor intensive and costly or relies on computational predictions that are often inaccurate. These limitations are alleviated by integration of structure probing data into prediction algorithms. However, existing algorithms are optimized for a specific type of probing data. Recently, new chemistries combined with advances in sequencing have facilitated structure probing at unprecedented scale and sensitivity. These nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 54 publications
0
75
0
Order By: Relevance
“…As shown in Fig. 2, when the base is paired, the sequence numbers of the paired bases are exchanged and stored in Y(X), then Y(X) = (1,14,13,12,5,6,7,8,9,10,11,4,3,2,15). Each mapping string Y(X) is a candidate solution, the solution with MFE is the optimal solution, which is the most stable secondary structure.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 2, when the base is paired, the sequence numbers of the paired bases are exchanged and stored in Y(X), then Y(X) = (1,14,13,12,5,6,7,8,9,10,11,4,3,2,15). Each mapping string Y(X) is a candidate solution, the solution with MFE is the optimal solution, which is the most stable secondary structure.…”
Section: Definitionmentioning
confidence: 99%
“…For the calculation of the free energy of RNA secondary structure, the stem energy is defined as a negative, the energy of loop is defined as a positive, and the free single strand does not participate. Deng found that the molecular free energy is related to a single complementary base pair, but adjacent base pairs also affect the free energy calculation of the molecule [5]. In the secondary structure prediction, if the free energy calculation of each part does not affect each other, the free energy of the entire structure is accumulated form the energy of each part, and the calculation principle is shown in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…It is pointed out in [135] that this simple metric is not informative enough, as it is heavily biased by performances of short RNAs. To resolve this issue, this study proposed to use a “sequence-length-weighted average” (SLW-average) to replace the plain average.…”
Section: Secondary Structure Predictionmentioning
confidence: 99%
“…showed, using mock-probe simulations, that Deigan et al . ‘s approach can give relatively poor performance when input data deviate from its assumed model [135]. To alleviate this problem and thereby provide broader applicability, several other methods have been developed.…”
Section: Data-directed Secondary Structure Predictionmentioning
confidence: 99%
“…Importantly, coverage disparities within transcriptome-wide data make them more prone to this deficiency, which can be remedied by sensible integration of coverage information. Resolving such ambiguity may also improve data-directed structure inference (Deng et al, 2016).…”
Section: Scope and Constraintsmentioning
confidence: 99%